Perceptual and motor inhibition in individuals with vestibular disorders. - Mohammad MT; Whitney SL; Sparto PJ; Jennings JR; Furman JM (Journal of Neurologic Physical Therapy, 2010)
Background and Purpose: Vestibular dysfunction has been shown to be associated with altered cognitive function. The purpose of this study was to examine changes in cognitive function in participants with vestibular disease during the course of vestibular physical therapy. Methods: Twenty-two participants (mean age = 52, standard deviation = 11) with previously diagnosed vestibular disorders were tested at the beginning and end of rehabilitation. The Motor and Perceptual Inhibition Test (MAPIT) was used to assess manual reaction times when responding to various stimuli presented on a computer screen. Additional physical performance measures and questionnaires related to dizziness, fear of falling, and activities of daily living were used to quantify change during the 6-week intervention period. The repeatable battery for the assessment of neuropsychological status (a measure of memory and executive function) was used to ensure that participants did not have memory or executive function deficits. Results: Overall, there were no significant differences in MAPIT score before versus after physical therapy intervention, however there were some participants who demonstrated improvements in motor inhibition (MI) and perceptual inhibition (PI) scores. Interstingly, 8 of the 9 participants with abnormal caloric test findings had improvements on 2 of the PI scores. Overall 50% to 64% of the participants demonstrated improvement in the 4 different MAPIT scores. There were improvements in physical performance and self-report measures at the end of the 6-week physical therapy intervention program. Discussion/Conclusion: Individuals with vestibular disorders may show improvement in MI and PI after a 6-week physical therapy intervention program; those with abnormalities on caloric and rotational chair tests appear especially likely to experience improvement in PI. Additional study is needed to determine whether individuals with vestibular disorders have remediable deficits in MI and PI.